Using the community pharmacy to identify patients at risk of poor asthma control and factors which contribute to this poor control - Armour, C.; LeMay, K.; Saini, B.; Reddel, H.; Bosnic-Anticevich, S.; Smith, L.; Burton, D.; Song, Y.J.; Alles, M.; Stewart, K.; Emmerton, Lynne; Krass, I. (Marcel Dekker, 2011)
Background: Although asthma can be well controlled by appropriate medication delivered in an appropriate way at an appropriate time, there is evidence that management is often suboptimal. This results in poor asthma control, poor quality of life, and significant morbidity. Methods: The objective of this study was to describe a population recruited in community pharmacy identified by trained community pharmacists as being at risk for poor asthma outcomes and to identify factors associated with poor asthma control. It used a cross-sectional design in 96 pharmacies in metropolitan and regional New South Wales, Victoria, Queensland, and Australian Capital Territory in Australia. Community pharmacists with specialized asthma training enrolled 570 patients aged ≥18 years with doctor-diagnosed asthma who were considered at risk of poor asthma outcomes and then conducted a comprehensive asthma assessment. In this assessment, asthma control was classified using a symptom and activity tool based on self-reported frequency of symptoms during the previous month and categorized as poor, fair, or good. Asthma history was discussed, and lung function and inhaler technique were also assessed by the pharmacist. Medication use/adherence was recorded from both pharmacy records and the Brief Medication Questionnaire (BMQ). Results: The symptom and activity tool identified that 437 (77%) recruited patients had poor asthma control. Of the 570 patients, 117 (21%) smoked, 108 (19%) had an action plan, 372 (69%) used combination of inhaled corticosteroid (ICS)/long-acting β2-agonist (LABA) medications, and only 17–28% (depending on device) used their inhaler device correctly.In terms of adherence, 90% had their ICS or ICS/LABA dispensed <6 times in the previous 6 months, which is inconsistent with regular use; this low adherence was confirmed from the BMQ scores. A logistic regression model showed that patients who smoked had incorrect inhaler technique or low adherence (assessed by either dispensing history or BMQ) and were more likely to have poor control. Conclusion: Community pharmacists were able to identify patients with asthma at risk of suboptimal control, and factors that contributed to this were elicited. This poorly controlled group that was identified may not be visible or accessible to other health-care professionals. There is an opportunity within pharmacies to target poorly controlled asthma and provide timely and tailored interventions.